TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN (PENUMPANG) PESAWAT UDARA - TITIN TITAWATI; ALINE FEBRIYANI LOILEWEN; GDE TUSAN ARDIKA (Universitas Mahasaraswati Mataram, 2021)
The development in the transportation sector, both goods, and services, especially transportation/ transportation using aircraft, is very rapid, it can be seen from the large number of business actors engaged in the aviation business. However, this is not balanced with good service to consumers, airlines have recently made unilateral flight cancellations or cancellations of flights for various reasons. This causes losses for passengers as consumers. This study aims to determine how the responsibility of business actors towards consumers/ passengers who suffer losses due to flight cancellations and legal remedies that can be taken by consumers. This study uses a form of normative legal research, which is research-based on written regulations and legislation and various literature related to the issues to be discussed in this study. An airline as a business actor can be held accountable if it makes a mistake. There are several types of responsibility in law, including responsibility in the sense of responsibility or also called moral responsibility, and responsibility in the sense of liability or also called juridical responsibility. The form of airline responsibility to passengers is included in the form of responsibility based on the element of error (liability based on fault) which is based on the principle of absolute responsibility (strict liability). The onrechtmatige daad doctrine is the basis for the formation of the principle of absolute responsibility as stated in article 1365 of the Civil Code which focuses on fault elements.